Las descripciones de B/V en las ortografías del siglo XVI - Maquieira Rodríguez, Marina A. (Estudios humanísticos. Filología, 1990)
This paper tries to establish the caracterising criteria used by authors of orthographic texts in the 16th century concerning to there elements in the classifications proposedat the time.Generally, the criteria employed in the definition of both letters are those of perceptibility and syllabic function, in as much as they being members of the consonants group. In their particular exposition, it is nevertheless observed a use of different articulatory criteria (place of articulation, manner of articulation, and articulatory tension); and the relationship between their pronunciation and that of sounds of the same of the same or other languages.